2020
DOI: 10.12681/psy_hps.25340
|View full text |Cite
|
Sign up to set email alerts
|

“Positive Relationships” and their impact on wellbeing: A review of current literature

Abstract: Positive relationships are widely considered to be one of the pillars of well-being. Their boosting effect on emotional and physical health has repeatedly been documented by experimental and longitudinal studies. Despite their instrumental role, the existing literature does not offer systematic observations of their nature and characteristics. In this paper, we aim to explore the specific characteristics of positive relationships. We conducted a thorough research of the existing most recent literature and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The literature review showed that, in general, adult friendship is positively correlated with individuals' wellbeing as well as most of its components. It has been documented that friendship is a valuable personal relationship among adults (Demir, 2015 ), contributes in various ways to their wellbeing (Pezirkianidis, 2020 ), enhances their resilience (Mertika et al, 2020 ; Pezirkianidis, 2020 ), and fulfills the fundamental human need for social interaction (Lyubomirsky, 2008 ). However, the instruments used in the previous literature to measure and conceptualize wellbeing significantly vary, i.e., the researchers focus on emotional, psychological, cognitive or subjective aspects of wellbeing making it difficult to draw conclusions and understand the nature of friendships' influences on wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review showed that, in general, adult friendship is positively correlated with individuals' wellbeing as well as most of its components. It has been documented that friendship is a valuable personal relationship among adults (Demir, 2015 ), contributes in various ways to their wellbeing (Pezirkianidis, 2020 ), enhances their resilience (Mertika et al, 2020 ; Pezirkianidis, 2020 ), and fulfills the fundamental human need for social interaction (Lyubomirsky, 2008 ). However, the instruments used in the previous literature to measure and conceptualize wellbeing significantly vary, i.e., the researchers focus on emotional, psychological, cognitive or subjective aspects of wellbeing making it difficult to draw conclusions and understand the nature of friendships' influences on wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Positive close relationships with family, friends and other significant people are also beneficial. They are found to be associated with emotional and instrumental support, intimacy, trust, increased sense of belonging and other protective indices of physical and psychological wellbeing (Carmichael et al, 2015 ; Mertika et al, 2020 ; Mitskidou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addiction recovery, this is especially important given the affected population are likely to have seen relationships breakdown, been subject to stigmatisation and experienced guilt and shame in respect of this (Avery and Avery, 2019). Outside of counteracting adversity, connectedness contributes to wellbeing through affirmative interaction with others in the shared experience of positive moments and responses (Mertika et al , 2020). Such positive relationships have been shown to increase happiness and improve life satisfaction in those who practise them (Mertika et al , 2020; Seligman, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Outside of counteracting adversity, connectedness contributes to wellbeing through affirmative interaction with others in the shared experience of positive moments and responses (Mertika et al , 2020). Such positive relationships have been shown to increase happiness and improve life satisfaction in those who practise them (Mertika et al , 2020; Seligman, 2019). Given this, positive relationships were designated as the PP strategy for the connectedness OPRI.…”
Section: Methodsmentioning
confidence: 99%
“…Half of them are friends while the others are spouses, lovers, parents, brothers and sisters but also colleagues, neighbours, coaches and counsellors. However, the qualities and content of a relationship characterized as positive have not yet been fully examined and described (Mertika et al, 2020).…”
Section: Introductionmentioning
confidence: 99%